Multidrug‐Resistant ESKAPEEc Pathogens From Bloodstream Infections in South Africa: A Cross‐Sectional Study Assessing Resistance to WHO AWaRe Antibiotics - Bakoena A. Hetsa; Jonathan Asante; Daniel G. Amoako; Akebe L. K. Abia; Joshua Mbanga; Sabiha Y. Essack (Health Science Reports, 2025)
ABSTRACT Background and Aims Multidrug‐resistant (MDR) pathogens, particularly members of the ESKAPE group and Escherichia coli (collectively referred to as ESKAPEEc), are major contributors to bloodstream infections (BSIs) and pose significant treatment challenges. This study aimed to characterize the antimicrobial resistance (AMR) profiles of ESKAPEEc isolates from BSIs in public hospitals in the uMgungundlovu District, South Africa, and to assess their resistance to World Health Organization (WHO) Access, Watch, and Reserve (AWaRe) antibiotics. Methods Between November 2017 and December 2018, blood samples (n = 195) were collected from adult and paediatric patients with suspected BSIs. Isolates were identified using the VITEK 2 system and confirmed by polymerase chain reaction (PCR). Antimicrobial susceptibility testing was performed using the Kirby–Bauer disk diffusion method and interpreted according to EUCAST/CLSI guidelines. The multiple antibiotic resistance index (MARI) was calculated. One‐way analysis of variance (ANOVA) was used to assess associations between MARI and clinical variables, including ward type and facility level. Results Out of 195 presumptive isolates, 159 were confirmed as ESKAPEEc. The most frequently identified pathogens were Klebsiella pneumoniae (28.9%) and Staphylococcus aureus (28.3%). High resistance rates were observed across WHO Access and Watch antibiotics, including ampicillin (76% in E. coli), gentamicin (67.4% in K. pneumoniae), and ciprofloxacin (≥ 60% in most species). Carbapenem resistance in Acinetobacter baumannii reached 90%. Overall, 94.9% of isolates were MDR, and 93.1% had MARI ≥ 0.2. Significant differences in MARI values were observed across ward groups and facility levels, with the highest values recorded in intensive care units (mean = 0.67, 95% CI: 0.62–0.72) and tertiary hospitals (mean = 0.64, 95% CI: 0.60–0.68), compared to regional hospitals (mean = 0.52, 95% CI: 0.47–0.57). Conclusion The findings reveal a high burden of MDR ESKAPEEc in BSIs and widespread resistance to WHO Watch antibiotics. Targeted antimicrobial stewardship and the implementation of microbiology‐guided therapy are urgently needed to optimize patient outcomes and curb the spread of resistance.